2003
DOI: 10.1249/01.mss.0000069754.07541.d2
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Loop Dysfunction in Quadriceps on the Contralateral Side in Patients with Ruptured ACL

Abstract: The abnormal response to prolonged vibration stimulation could represent abnormal gamma loop in the quadriceps femoris muscle of the uninjured side in patients with ACL rupture since the normal response of maximal voluntary contraction and I-EMG to prolonged vibration stimulation could not be evoked without normal function of the gamma loop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
71
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 13 publications
13
71
0
4
Order By: Relevance
“…Our current results combined with those of others [21,22] who have demonstrated neuromuscular control changes at joints proximal to involved ankles provide evidence that the etiology of CAI involves alteration in the central nervous system control of lower extremity neuromuscular function. There is mounting evidence of central neuromuscular alterations in response to unilateral joint injuries with reports in the literature describing the phenomenon in patients with acute ankle sprain [7], anterior cruciate ligament injury [23,24], and shoulder impingement syndrome [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our current results combined with those of others [21,22] who have demonstrated neuromuscular control changes at joints proximal to involved ankles provide evidence that the etiology of CAI involves alteration in the central nervous system control of lower extremity neuromuscular function. There is mounting evidence of central neuromuscular alterations in response to unilateral joint injuries with reports in the literature describing the phenomenon in patients with acute ankle sprain [7], anterior cruciate ligament injury [23,24], and shoulder impingement syndrome [25].…”
Section: Discussionmentioning
confidence: 99%
“…Impaired motor control contralateral to the side of injury may be mediated via gamma motoneuron loops [23]. Gamma motoneurons innervate muscle spindles which are sensory organs within skeletal muscles that are perceptive to changes in muscle length.…”
Section: Discussionmentioning
confidence: 99%
“…Esses dados contradizem a idéia de alguns estudos 7,10,11,15,22,23 segundo os quais o MNA não poderia ser utilizado como referência nas avaliações do membro acometido após reconstrução do LCA. Alguns autores 10,23 sugerem que a diminuição das informações sensoriais após a lesão do LCA não teria um impacto direto sobre a função dos motoneurônios alfa, mas sobre a função dos motoneurônios gama.…”
Section: Discussionunclassified
“…Estudos encontraram esse deficit no membro não-acometido de indivíduos com ruptura e submetidos à reconstrução de LCA 7,11 . A similaridade entre diferentes estudos aponta para um mecanismo neurofisiológico comum.…”
unclassified
“…Failure of voluntary activation from the central nervous system to the quadriceps muscle as a result of disruption of the ACL has been implicated [74]. Konishi et al have found abnormal gamma loop function in the involved and uninvolved quadriceps muscle of patients with ACL rupture [75]. There is loss of feedback from ACL mechanoreceptors which results in a suppressed state of recruitment of high-threshold motor units, presumably through the elimination of feedback to gamma motor neurons [76].…”
Section: Causes Of Quadriceps Weaknessmentioning
confidence: 99%